Experimental study on the influence of the injection structure on solid scramjet performance. (November 2021) - Yang, Pengnian; Xia, Zhixun; Ma, Likun; Chen, Binbin; Feng, Yunchao; Zhang, Jiarui
Abstract: Injection structures can affect the ignition and combustion of fuel and supersonic air in scramjets, strongly impacting their performance. The influence of three different injection structures on the performance of a solid scramjet was investigated using direct-connect tests. The experiment employed a boron-based fuel-rich propellant and simulated a flight Mach number 5.6 at 25 km. The results show that, compared to a circular nozzle (test no.1), the elliptical nozzle (test no.2) can significantly improve the ignition and combustion of the fuel-rich mixture produced in the gas generator. This improvement is even more significant when a two-stage elliptical nozzle is adopted (test no. 3). The combustion of the fuel-rich mixture presents the typical cycle of establishment, development, maintenance, and decay. The wall ablation area and particle deposition distribution, show that the gaseous components in the fuel-rich mixture burn rapidly, and that particles deposition increases when an elliptical nozzle is used. The combustion efficiency of test no.3 reached 0.60, which is larger than the 0.48 obtained during test no.1. The low particle combustion efficiency is a key factor limiting solid scramjets performance. Highlights: The injection structures do affect the performance of the solid scramjet. The elliptical nozzle can significantly solve the problem of fuel-rich mixture ignition delay. The combustion has the characteristics of an establishment-development-maintenance-decay cycle.